Analysis of algebraic thinking ability viewed from the mathematical critical thinking ablity of junior high school students on problem based learning - Harti, Laela Sih; Agoestanto, Arief (Department of Mathematics, Universitas Negeri Semarang, 2019)
The aims of this research are (1) find out students critical ability in learning problem based learning achieves the minimal mastery criteria; (2) find out students algebraic ability in learning problem based learning achieves the minimal mastery criteria; (3) to describe the algebraic ability of 8th grade students of SMP Negeri 6 semarang viewed by students critical ability (high, middle, and low). The method of this research is mix method with concurrent embedded design. The population in this researchwere class 8thSMP Negeri 6 Semarang The research sample was class VIII G and the subjects were taken 9 out of 34 students of class VIII G. The results of the research showed that: (1) students critical thinking ability in problem based learning achieved the minimal mastery criteria; (2) students algebraic thinking ability in problem based learning achieved the minimal mastery criteria; (3) students who belonging to the high-critical thinking ability group, have high generationaland global meta-level capabilities, while transformational capabilities that moderate to high.Studentswho belonging to the middle-critical thinking ability group, have generational, transformational, and global meta-level capabilities that tend to be moderate. Studentswho belonging to the low-critical thinking ability group, have generational and transformational capabilities that tend to be low, while global meta-level capabilities that low to moderate.